Pengaruh Pembangunan Jalan terhadap Perubahan Penggunaan Lahan - Zulqadri Ansar; Ananto Yudono; Isfa Sastrawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2014)
The growth of cities is in line with the development of transportation technology. Land use change, especially residential area tend to follow the availability of the transport network. Transportation and land use are closely related and have specific purpose in planning. The purpose of transportation system planning is to provide facilities for the movement of passengers and goods from one place to another. While the purpose of land use planning is to achieve the function of the buildings. Mamminasata region, the one of metropolitan cities in Indonesia, including Makassar City, Sungguminasa City, Maros Regency and Takalar Regency, should have an integrated planning for transportation sector. Development of Mamminasata region led to the new activity centers and new settlements such as the new Hertasning road. New Hertasning Street is the corridor that connect Makassar City and Sungguminasa City (Gowa Regency) in the southeast of the Mamminasata Region. The development of the new road changed agriculture uses to residential uses. This study examines the effect of development of new road toward land use changes. Land use changes using three variables: changes in land use, land use intensity and land price. This study used data inventory, comparative and mapping overlay analysis. The result of this analysis indicates the development of new road caused land use change along the corridor.